Pengembangan Soft Skills Komunikasi Interpersonal Mahasiswa dalam Program Kampus Mengajar: Analisis Teori Difusi Inovasi - Laisya Josefhani Putri; Ummu Salamah; Annisa Husnusyifa (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study explores how students develop their interpersonal communication skills through the Kampus Mengajar program at Universitas Garut. The focus is on how students adapt and learn to communicate within their partner school environments, and how the program’s duration and social support play a role in this process. Using a qualitative approach, data were gathered through interviews, observations, and documentation.Findings reveal that the development of interpersonal communication soft skills occurs gradually and is strongly influenced by sufficient adaptation time, support from supervisors, school teachers, peer interactions, and community engagement. The process involves not only technical communication aspects but also building warm, trusting, and empathetic relationships. Students learn to adjust their communication style according to the characteristics and needs of students as well as the surrounding cultural environment. Intensive interaction and ongoing guidance are key factors in strengthening students’ interpersonal communication skills during the program. These findings illustrate that developing soft communication skills is a dynamic process involving various social elements and adequate time.